Study on Mechanical Properties and Acoustic Emission Characteristics of Sandstone under Freezing and Thawing - Ziyi Wang; Ping Liu; Chang Luo; Yichao Jia; Zhen Chen (Advances in Materials Science and Engineering)
The cyclic freezing-thawing action in cold regions leads to the deterioration of rock damage, resulting in local damage and further threatening the safety of engineering. In order to study the degradation characteristics of green sandstone and yellow sandstone under freeze-thaw cycles from macroscopic and microscopic aspects, the sandstone of a mining area in Inner Mongolia was used as experimental material. The freeze-thaw cycles were divided into 20 times, 30 times, and 40 times. NMR images and mechanical test results of two different rock samples were analyzed by binarization, NMR, and mechanical test. The test results show that, except that the mass change is less than that of yellow sandstone, the physical index degradation degree of green sandstone is higher than that of yellow sandstone, and the frost resistance is less than that of yellow sandstone. The change of acoustic emission event rate of green sandstone is mainly in the elastic deformation stage and stable crack propagation stage, and the change of acoustic emission event rate of yellow sandstone is concentrated in the crack closure stage. In the loading process, the energy release trends of the two sandstones are similar; the 30 freeze-thaw cycles are the boundary of brittle-plastic transformation of green sandstone, and the increase of cumulative energy is the most obvious. The research results provide a theoretical basis for studying the rock failure mechanism and improving the stability of rock engineering in cold regions.